2002
DOI: 10.1128/jvi.76.14.7247-7254.2002
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of Latent Cytomegalovirus Infection in Mouse Brain Cells Detected after Transfer to Brain Slice Cultures

Abstract: Cytomegalovirus (CMV) is the most significant infectious cause of brain disorders in humans involving the developing brain. It is hypothesized that the brain disorders occur after recurrent reactivation of the latent infection in some kinds of cells in the brains. In order to test this hypothesis, we examined the reactivation of latent murine CMV (MCMV) infection in the mouse brain by transfer to brain slice culture. We infected neonatal and young adult mice intracerebrally with recombinant MCMV in which the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 62 publications
1
28
0
1
Order By: Relevance
“…Instead, the current data suggest that neural stem cells might constitute the site of latency in the CNS. Indeed, when brain slices from latently infected mice were cultured for extended periods of time, reactivated murine CMV IE expression was mainly detected in immature neural stem cells lining the ventricular cavities (41). Our observations that the HCMV genome persisted in individual pNSCs in vitro for an extended period of time support the idea that cells in the early stages of neural development might constitute a reservoir of virus in the CNS.…”
Section: Discussionsupporting
confidence: 71%
“…Instead, the current data suggest that neural stem cells might constitute the site of latency in the CNS. Indeed, when brain slices from latently infected mice were cultured for extended periods of time, reactivated murine CMV IE expression was mainly detected in immature neural stem cells lining the ventricular cavities (41). Our observations that the HCMV genome persisted in individual pNSCs in vitro for an extended period of time support the idea that cells in the early stages of neural development might constitute a reservoir of virus in the CNS.…”
Section: Discussionsupporting
confidence: 71%
“…Furthermore, the clinical manifestations on some animal models are different from those observed in the human central nervous system (CNS) (Woolf et al 2007). Nevertheless, these animal models have provided evidence that the highest CMV susceptibility in CNS is presented by neural precursor cells (NPCs) (Tsutsui et al 2002). Infection of these cells might be the cause of microcephaly and mental retardation since it has been observed that murine CMV inhibits NPC proliferation and migration (Shinmura et al 1997;Tsutsui et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Murine CMV latency is not limited to cells of myeloid lineage (23,60), and the same might be true for HCMV. The periventricular location of neuronal-cell precursors from which murine CMV reactivates upon culturing of latently infected mouse brain explants (60) is reminiscent of HCMV's proclivity for subependymal neuronal cells in the ventriculoencephalitis that results from HCMV reactivation in persons with advanced AIDS (5,64).…”
mentioning
confidence: 99%
“…The periventricular location of neuronal-cell precursors from which murine CMV reactivates upon culturing of latently infected mouse brain explants (60) is reminiscent of HCMV's proclivity for subependymal neuronal cells in the ventriculoencephalitis that results from HCMV reactivation in persons with advanced AIDS (5,64). The mechanisms that underlie HCMV reactivation disease in the central nervous system are unknown, though terminal differentiation of the neuronal lineage is linked to permissiveness for HCMV replication (43).…”
mentioning
confidence: 99%